UJI ANTIBAKTERI EKSTRAK ETANOL DAGING BUAH PALA (Myristica Fragrans Houtt.) TERHADAP BAKTERI STAPHYLOCOCCUS AUREUS DAN ESCHERICHIA COLI - Barry Roseveld Joseph Siegers; Eka Astuty; Yuniasih M.J. Taihuttu (Fakultas Kedokteran Universitas Pattimura, 2022)
Infectious diseases are still a serious problem in developing countries. Infectious diseases can be treated with antibacterial use. If the irrational use of antibacterials will lead to antibiotic resistance. Nutmeg is a plant that has antibacterial potential. The purpose of this study was to determine the inhibition of the ethanol extract of the nutmeg pulp. The concentrations of the ethanol extract used were 25%, 50%, 75% and 100%. Antibacterial activity test against Staphylococcus aureus and Escherichia coli using the disc diffusion method. The test results showed that all concentrations of ethanol extract had the ability to inhibit the growth of Staphylococcus aureus and Escherichia coli with concentrations of 25%, 50%, 75% and 100% with each inhibition zone for Staphylococcus aureus being 31.4 mm; 36.8 mm; 38.9 mm; 39.1 mm; 43.9 mm, meanwhile Escherichia coli bacteria have an inhibition zone of 14.3 mm; 19.8 mm; 28.9 mm; 32.1 mm; 36.9 mm.